Extending the structure of an ABC transporter to atomic resolution: modeling and simulation studies of MsbA. - Campbell, J; Biggin, P; Baaden, M; Sansom, MS (2003)
Molecular modeling and simulation approaches have been use to generate a complete model of the prokaryotic ABC transporter MsbA from Escherichia coli, starting from the low-resolution structure-based Calpha trace (PDB code 1JSQ). MsbA is of some biomedical interest as it is homologous to mammalian transporters such as P-glycoprotein and TAP. The quality of the MsbA model is assessed using a combination of molecular dynamics simulations and static structural analysis. These results suggest that the approach adopted for MsbA may be of general utility for generating all atom models from low-resolution crystal structures of membrane proteins. Molecular dynamics simulations of the MsbA model inserted in a fully solvated octane slab (a membrane mimetic environment) reveal that while the monomer is relatively stable, the dimer is unstable and undergoes significant conformational drift on a nanosecond time scale. This suggests that the MsbA crystal dimer may not correspond to the MsbA dimer in vivo. An alternative model of the dimer is discussed in the context of available experimental data.